2012
DOI: 10.1007/s00264-012-1580-z
|View full text |Cite
|
Sign up to set email alerts
|

Sagittal placement of the femoral component in total knee arthroplasty predicts knee flexion contracture at one-year follow-up

Abstract: Purpose Flexion contracture has been shown to impair function and reduce satisfaction following total knee arthroplasty (TKA). The aim of this study was to identify modifiable intraoperative variables that predict post-TKA knee extension. Methods Data was collected prospectively on 95 patients undergoing total knee arthroplasty, including pre-operative assessment, intra-operative computer assisted surgery (CAS) measurements and functional outcome including range of motion at one year. Patients were divided int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 32 publications
0
34
0
Order By: Relevance
“…Studies by Kim et al 29 and Gromov et al 30 showed that the sagittal alignment of the femoral component of >3 degrees flexion significantly increased component failure, whereas Lustig et al found that a posterior slope of >3.5 degrees produced a threefold increase in the risk of mild flexion. 31 Currently, most researches, including the studies included in this metaanalysis, still generally consider 2 or 3 degrees as cutoff values for alignments, and both these degrees were used in our study. The results of the present meta-analysis showed that significantly fewer patients come with a tibial component alignment out of AE3 degrees, femoral coronal angle out of AE3 degrees°, and overall mechanical alignment out of AE3 degrees in PAD than in CON.…”
Section: Discussionmentioning
confidence: 99%
“…Studies by Kim et al 29 and Gromov et al 30 showed that the sagittal alignment of the femoral component of >3 degrees flexion significantly increased component failure, whereas Lustig et al found that a posterior slope of >3.5 degrees produced a threefold increase in the risk of mild flexion. 31 Currently, most researches, including the studies included in this metaanalysis, still generally consider 2 or 3 degrees as cutoff values for alignments, and both these degrees were used in our study. The results of the present meta-analysis showed that significantly fewer patients come with a tibial component alignment out of AE3 degrees, femoral coronal angle out of AE3 degrees°, and overall mechanical alignment out of AE3 degrees in PAD than in CON.…”
Section: Discussionmentioning
confidence: 99%
“…The potential consequences include: an asymmetrical flexion gap [4,5]; contractures [6]; persistent instability, particularly in flexion with lift-off [7][8][9]; unilateral wear of the polyethylene inlay [10]; postoperative pain [11]; and early implant failure [5,[12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of the literature that does exist, it is generally accepted that the femoral component should be placed in 0° to 3° of flexion relative to the mechanical axis. 4,22,23 However, there is significant variation in the techniques used to determine femoral component flexion, and a clear consensus on the ideal alignment of the femoral component in the sagittal plane is lacking. 24 Ideally, flexion of the femoral component of a total knee prosthesis should recreate the native anatomy, barring pathology, of the distal femur in the sagittal plane.…”
Section: Discussionmentioning
confidence: 99%
“…9 Additionally, malalignment in the sagittal plane can alter femoral component sizing, contribute to a prolonged recovery, and decrease survivability of a total knee prosthesis. 1,18,23,26,27 Navigation during TKA is becoming increasingly popular because the literature has shown its use assists in accurate component placement and reduces the incidence of outliers compared with the use of standard instrumentation in TKA. [28][29][30][31][32][33][34] Data from the Australian registry showed increased survivorship in a subset of patients who underwent navigated TKA.…”
Section: Discussionmentioning
confidence: 99%